Preparação, propriedades e performance fotocatalítica de novos compósitos mesoporosos: TiO2-Ce:SiO2 - Iwasaki, Mariana Tiemi [UNIFESP] (2017)
TiO2:SBA-15 (TiSBA) e TiO2-CeO2:SBA-15 (TiCeSBA) composites were synthesized by direct synthesis (DS) and post-synthesis (PS) methods using Pluronic® P123 (EO20PO70EO20) as a structure-directing agent, in acidic solution, tetraethyl orthosilicate (TEOS), titanium (IV) isopropoxide and cerium (III) nitrate hexahydrate as the source of SiO2, TiO2 and CeO2, respectively. The composites obtained were characterized by several physical-chemical techniques and the results showed that all of them have a two-dimensional hexagonal mesoporous structure, characteristic of SBA-15. It was also verified that the composites prepared by DS presented higher surface area, pore volume, pore size and crystallinity, when compared to those obtained by PS. However, they had a mixed phase of anatase and rutile, whereas, those obtained by PS, there were a single-phase anatase formation. The composites obtained were used as photocatalysts in the degradation of phenol (100 mg L-1 of carbon) and methyl orange (10-50 mg L-1 of carbon) as model of organic pollutants present in aqueous systems. In these tests, medium pressure mercury lamp (125 W) was used as source of UV radiation, air (4 L min-1 flow), 400 mL reactor, commercial TiO2 (50 and 400 mg L-1 ), pH ≈ 4,5 and 3, composites TiSBA.SD, TiSBA.PS and TiCeSBA.PS (400 and 1600 mg L-1). The degradation of the pollutants, along the reaction time, was evaluated using the total organic carbon analyzer (TOC) and absorption spectroscopy in the UV-Vis region. The composites of TiSBA.SD and TiSBA.PS did not show significant photocatalytic activity in comparison to TiP25 in the phenol mineralization. However, under the studied conditions, TiSBA.SD, TiSBA.PS and TiCeSBA.PS composites showed to be efficient for degradation of the orange methyl dye, mainly at pH 3, showing that this parameter is an important factor.